Modeling and Design of Flexible Pavements and Materials - Little, Dallas N.; Allen, David H.; Bhasin, Amit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This textbook lays out the state of the art for modeling of asphalt concrete as the major structural component of flexible pavements. The text adopts a pedagogy in which a scientific approach, based on materials science and continuum mechanics, predicts the performance of any configuration of flexible roadways subjected to cyclic loadings. The authors incorporate state-of the-art computational mechanics to predict the evolution of material properties, stresses and strains, and roadway deterioration. Designed specifically for both students and practitioners, the book presents fundamentally complex concepts in a clear and concise way that aids the roadway design community to assimilate the tools for designing sustainable roadways using both traditional and innovative technologies.
Introduction -- Part 1. Materials -- Asphalt Binders -- Aggregates -- Surface Properties -- Additives and Modifiers -- Asphalt Mastics -- Asphalt Mixtures -- Failure Mechanisms -- Part 2. Mechanics -- Mechanics of Continuous Solids -- One Dimensional Constitutive Theory -- Elasticity and Thermoelasticity -- Viscoelasticity and Thermoviscoelasticity -- Plasticity, Viscoplasticity and Fracture -- Computational Methods for Roadway Analysis and Design -- Computational Modeling Applications.
Keywords: Building materials; Mechanics, Applied; Solids; Microtechnology; Microelectromechanical systems; Engineering geology; Transportation engineering; Traffic engineering; Building Materials; Structural Materials; Solid Mechanics; Microsystems and MEMS; Geoengineering; Transportation Technology and Traffic Engineering